Perlindungan Hukum Terhadap Nasabah BMT Asyiffa Kec. Sekampung Lampung Timur Yang Diliquiditasi - ayu franita putri (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Meto, 2019)
BMT is microfinance institution with sharia principles, BMT ia present in giving a sudden spotlight on the welfare of small communities such as BMT Asyiffa, but BMT Asyiffa is curently giving disapointment to members and custumers and trust in welfare matters is lost because the BMT is liquidate. And from the consequences of liquidation, it requeres a protection for BMT customers. To avoid this caos, we can see that the protection of BMT can be seen based on LOw No. 1 of 2013 and Cooperative Law No. 25 of 1992 and we can analyze it with a Consumer Protection Act No. 8 of 1999 which can provide an answer to the unrest of the problem. which is very disturbing to the community. In this case we can see that the problem that is quite urgent is where the inability of a microfinance intitution can be seen from the human resources in managing a financial institution that is not relevant to the provisions that should, and the gap between legal knowlage they have not been able to overcome various problems exist because they only run a BMT with basic capabilities without seeing a risk in front of them.